Malesherbiaceae endémicas del Perú - León, Blanca (2006)
The Malesherbiaceae are represented in Peru by ten species in the genus Malesherbia (Brako & Zarucchi, 1993), all herbs and subshrubs. Here we recognize all these taxa as endemics. Endemic Malesherbiaceae are found in the Mesoandean, Desert Shrubland and Subtropical Costal Desert regions, between 300 and 3600 m elevation. None of the species has been collected to date within Peru’s protected areas system.